SOME GEOLOGICAL OBSERVATIONS ON THE ARCHEAN NAPIER COMPLEX AT MT. RIISER-LARSEN, AMUNDSEN BAY, ENDERBY LAND - マキモト, ヒロシ; アサミ, マサオ /; MAKIMOTO, Hiroshi; ASAMI, Masao; GREW, Edward S. (National Institute of Polar Research, 1989)
P(論文) The summer party of the 29th Japanese Antarctic Research Expedition (JARE-29,1987-1988) performed a brief geological survey at Mt. Riiser-Larsen in Enderby Land, East Antarctica. The Mt. Riiser-Larsen area is underlain by various kinds of granulite-facies metamorphic rocks of the Archean Napier Complex with minor mafic dike rocks. Metamorphic rocks are composed mainly of felsic gneiss with subordinate pyroxene granulite, pelitic gneiss and quartzite. Magnetite-rich rock (metaironstone) and pyroxenite crop out sporadically. Metamorphic rocks show a well-layered sequence due to the difference of lithologies, indicating that most of the metamorphic rocks were derived from sedimentary rocks. By and large, layering of the metamorphic rocks trends E-W to NE-SW, and dips south homoclinally. The felsic gneiss is locally lineated, due to the preferred orientation of elongated quartz and feldspar grains. These lineations dip south gently. Two types of mesoscopic folds, and earlier isoclinal fold and a later open fold, are found. Mafic dikes, which include basalt and dolerite, discordantly intrude the metamorphic rocks throughout the area. All the mafic dikes are weakly metamor-phosed but igneous textures are well preserved, and the dikes are not folded. They were emplaced after the main stage of the granulite-facies Napier metamor-phism and folding. These mafic dikes can be regarded as members of the Amundsen Dikes. departmental bulletin paper